2022
DOI: 10.3390/biology11111611
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Diversity and Evolutionary Relatedness of Paulownia Witches’-Broom Phytoplasma in Different Geographical Distributions in China

Abstract: To reveal the distribution and transmission pathway of Paulownia witches’-broom (PaWB) disease, which is caused by phytoplasmas related to genetic variation, and the adaptability to the hosts and environments of the pathogenic population in different geographical regions in China, in this study, we used ten housekeeping gene fragments, including rp, fusA, secY, tuf, secA, dnaK, rpoB, pyrG, gyrB, and ipt, for multilocus sequence typing (MLST). A total of 142 PaWB phytoplasma strains were collected from 18 provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…The phylogenetic analysis was performed through the sequence analysis of 10 housekeeping genes, namely 16S rRNA, rp, fusA, secY, tuf, secA, dnaK, rpoB, pyrG, gyrB and ipt. The results showed that the 142 PaWB phytoplasma strains clustered into two main lineages with obvious geographical differentiation [28].…”
Section: The Paulownia Witches' Broom Phytoplasmamentioning
confidence: 99%
“…The phylogenetic analysis was performed through the sequence analysis of 10 housekeeping genes, namely 16S rRNA, rp, fusA, secY, tuf, secA, dnaK, rpoB, pyrG, gyrB and ipt. The results showed that the 142 PaWB phytoplasma strains clustered into two main lineages with obvious geographical differentiation [28].…”
Section: The Paulownia Witches' Broom Phytoplasmamentioning
confidence: 99%